High perianal fistula: a narrative review of common management techniques - Micallef, Jess; Barns, Mitchell (International Surgery Journal, 2022)
Perianal fistula is a common and problematic condition that results in perianal pain, recurrent infection, anal discharge and overall reduced quality of life. Low perianal fistula, those that involve the lower third of the external anal sphincter, are relatively easily managed with the use of a fistulotomy. However, high perianal fistula, ones that involve the upper two thirds of the external anal sphincter are extremely difficult to treat. There is no consensus on best management of these type of fistula with little high-quality evidence to guide management. We perform a narrative review of recent literature on common surgical techniques and provide an opinion of the utility of each to guide management.